THE ACCURACY OF ALTERNATIVE TRIAGE RULES FOR IDENTIFICATION OF SIGNIFICANT TRAUMATIC BRAIN INJURY: A DIAGNOSTIC COHORT STUDY. Issue 10 (7th September 2013) - Fuller, G W; Woodford, M; Lawrence, T; Coats, T; Lecky, F
Abstract : Objectives & Background: Traumatic brain injury (TBI) is a leading cause of death and disability in young adults. Reorganisation of trauma services with direct triage of suspected head injury patients to trauma centres may improve outcomes following TBI. This study aimed to determine the sensitivity of principal English triage tools for identifying significant TBI. Methods: We performed a diagnostic cohort study using data prospectively collated from the Trauma Audit and Research Network database between 2005–2011. Adult head injury patients were retrospectively classified according to London Ambulance Service (LAS) and Head Injury Transportation Straight to Neurosurgery study (HITS-NS) triage criteria. Sensitivity and specificity were then calculated against a reference standard of significant TBI, comprising head region abbreviated injury score (AIS) ≥3 or neurosurgical operation. To investigate the determinants of triage rule sensitivity patient characteristics were compared between true positive and false negative groups using descriptive statistics and hypothesis testing. Additional analyses were conducted to explore the robustness of results to selection bias and examine the sensitivity of pre-hospital Glasgow Coma Score (GCS) for detecting significant TBI. Results: 6, 559 patients were included in complete case analyses. The LAS and HITS-NS triage tools demonstrated sensitivities of 44.5% (95% CI 43.2–45.9) and 32.6% (95% CI 31.4–33.9) respectively for identifying significant TBI patients. These results were not materially changed following multiple imputation of missing data under a missing at random assumption. False negative significant TBI cases were relatively older, more likely to be female, more frequently secondary to low-level falls, and were less likely to have very severe AIS 5 or 6 head injuries, p<0.01. Pre-hospital GCS did not appear to be a sensitive discriminator for identifying significant TBI, with 44.9% of patients classified as having significant TBI presenting with a PH GCS of ≥13. Conclusion: considerable proportion of significant head injury patients may not to be triaged directly to trauma centres. Investment is therefore necessary to improve the accuracy of existing triage rules and maintain expertise in TBI diagnosis and management in non-specialist emergency departments.